A novel process for the production and separation of heavier hydrocarbons from sorbitol-derived oil. (15th June 2015) - Lv, Dong-Can; Liu, Yun-Quan; Zhu, Shen-Jia; Ye, Yue-Yuan; Wang, Duo
Highlights: Production process for heavier hydrocarbons from sorbitol was developed. A novel separation process for eliminating 2-iodohexane byproduct with zinc powder was developed to get pure hydrocarbons. The reaction conditions for 2-iodohexane removal were studied and optimized. The obtained heavier hydrocarbons are mainly C12 and C18 hydrocarbons including alkanes, alkenes, and aromatics. The high heating value of the obtained heavier hydrocarbons is 43.5 MJ/kg, suitable for being used as transportation fuel. Abstract: A novel process for the production and separation of heavier hydrocarbons from sorbitol-derived oil was studied. 2-Iodohexane, the by-product of the reduction of sorbitol into hydrocarbons, was successfully removed by transforming it into hexane and hexenes after reacting with zinc. The eliminating reaction was completed in 45 min at the conditions of: a zinc/2-iodohexane molar ratio of 6:1, a reaction temperature of 120 °C, and an agitation speed of 1200 rpm. The heavier hydrocarbons obtained were mainly C12 and C18 alkanes, alkenes, and aromatics, which have a water content of 0.1% and a high heating value of 43.5 MJ/kg. Other physico-chemical properties of the heavier hydrocarbons were characterized with GC–MS, FT-IR and 1 H NMR. The approach developed in this work for the production and purification of heavier hydrocarbons from sorbitol-derived oil is relatively simple yet promising, which we believe could possibly become a new way for the production of transportation fuels from biomass sources.